Analysis of electromechanical coupling coefficient of surface acoustic wave resonator in ZnO piezoelectric thin film structure - Md Ralib @ Md Raghib, Aliza 'Aini; Nordin, Anis Nurashikin (IEEE, 2014)
An analysis of the electromechanical coupling coefficient for surface acoustic wave (SAW) devices developed in complementary metal oxide semiconductor (CMOS) is presented in this work. This SAW resonator uses zinc oxide (ZnO) as its piezoelectric thin film. The resonator's interdigitated electrodes were designed such that it produces 1 GHz resonance frequency. Finite element simulation of the CMOS SAW resonator was conducted using COMSOL Mutliphysics™. Three different analyses namely eigenfrequency, frequency domain and time domain analyses were conducted. The thicknesses of ZnO were varied from 2 μm to 5.5 μm with step size of 0.5 μm. Simulation results indicate maximum electromechanical coupling coefficient is achieved when normalized thickness is in the range of 0.63 <; (hzno/λ) <; 0.78. Experimental measurements were conducted on the fabricated CMOS SAW resonator and compared with the simulation results.